2009
DOI: 10.1111/j.1462-2920.2008.01838.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the metal specificity of the Pseudomonas aeruginosa pyoverdine–iron uptake pathway

Abstract: Pyoverdine (PvdI) is the major siderophore secreted by Pseudomonas aeruginosa PAOI in order to get access to iron. After being loaded with iron in the extracellular medium, PvdI is transported across the bacterial outer membrane by the transporter, FpvAI. We used the spectral properties of PvdI to show that in addition to Fe(3+), this siderophore also chelates, but with lower efficiencies, all the 16 metals used in our screening. Afterwards, FpvAI at the cell surface binds Ag(+), Al(3+), Cd(2+), Co(2+), Cu(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
156
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(170 citation statements)
references
References 60 publications
11
156
1
2
Order By: Relevance
“…Similar data were obtained with the Pvd uptake pathway in P. aeruginosa: there was a large metal specificity for the binding stage for FpvA, but only Cu 2ϩ , Ga 3ϩ , Mn 2ϩ , and Ni 2ϩ were transported and with uptake rates between 7-and 42-fold lower than that of Fe 3ϩ (6). This may be a common property of all siderophore outer membrane transporters.…”
Section: Discussionsupporting
confidence: 79%
“…Similar data were obtained with the Pvd uptake pathway in P. aeruginosa: there was a large metal specificity for the binding stage for FpvA, but only Cu 2ϩ , Ga 3ϩ , Mn 2ϩ , and Ni 2ϩ were transported and with uptake rates between 7-and 42-fold lower than that of Fe 3ϩ (6). This may be a common property of all siderophore outer membrane transporters.…”
Section: Discussionsupporting
confidence: 79%
“…3). In accordance with the published effects of metals on pyoverdine fluorescence (Braud et al, 2009), a hypochromic effect was observed when FeCl 3 (100 mM) was added to the samples, whereas the addition of CuSO 4 (100 mM) caused a hyperchromic effect (data not shown).…”
Section: Isolation and Characterization Of Differently Pigmented P Asupporting
confidence: 89%
“…The UV-vis absorption spectra obtained were compared to spectra of pigments already reported in the literature. The spectrum for pyomelanin was reported by Kurian et al (2014), those for phenazine-1-carboxylic acid (PCA) and pyocyanin by Mavrodi et al (2013) and that for pyoverdine by Braud et al (2009).…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…For instance, the Pseudomonas aeruginosa strain KUCd1, which also showed high Cd resistance, was reported to increase siderophore production when exposed to Cd (20). Similarly, Braud et al (54) found that the presence of Al, Cu, Ga, Mn, Ni, and Zn in the extracellular medium induced pyoverdine production in Pseudomonas aeruginosa PAO1, while Naik and Dubey (55) observed Pb-enhanced siderophore production when Pb-resistant Pseudomonas aeruginosa strain 4EA was cultured in a medium containing as much as 0.5 mM lead nitrate. In contrast, reduced siderophore production upon exposure to Cd (10 to 100 M) was observed in Bacillus amyloliquefaciens NAR38.1 by Gaonkar and Bhosle (56), together with severe inhibition of bacterial growth.…”
Section: Discussionmentioning
confidence: 90%